Improving Digital Literacy & Digital Marketing Skills of MSMEs in Bonto Manurung Village: Peningkatan Kemampuan Literasi Digital & Pemasaran Digital Pelaku UMKM di Desa Bonto Manurung - SAS, Abdillah; Syam, Supriadi; Syafaruddin, Andi Riska Andreani; Gunawang, Safitri Nuraulia; Alfarauq, Saddam (Universitas Lancang Kuning, 2024)
This community service program aims to enhance digital literacy and digital marketing skills among small business groups in Bonto Manurung village, Maros Regency. The lack of knowledge and skills in utilizing digital technology is one of the main obstacles to improving the competitiveness and market reach of these businesses. The program was conducted through training, technology implementation, and intensive mentoring focused on using websites for digital marketing, production management, marketplace creation and use, digital literacy, basic digital marketing, business model canvas, and digital content. Evaluation was carried out using pre-test and post-test questionnaires administered to the training participants. The results indicated an increase in participants' knowledge in various aspects, with improvements ranging from 40% to 100% after several training stages. Additionally, this program heightened awareness of the importance of digital literacy and digital media in managing businesses in the modern era.